The Characteristics of Summer Descending Sporadic E Layer Observed With the Ionosondes in the China Region. Issue 3 (23rd March 2021) - Qiu, Lihui; Zuo, Xiaomin; Yu, Tao; Sun, Yangyi; Liu, Huixin; Sun, Lingfeng; Zhao, Biqiang
Abstract: This work statistically analyzed the characteristics of the summer descending sporadic E layers (Es) recorded at four Chinese ionospheric sounding stations of Sanya (109.4°E, 18.3°N, and I: 24.1°), Wuhan (114.4°E, 30.5°N, and I: 45.5°), Beijing (116.2°E, 40.3°N, and I: 58.7°), Mohe (122.5°E, 52.0°N, and I: 69.6°), and simulated the vertical ion convergence derived from the Horizontal Wind Model (HWM14) for the period from June 1, 2014 to August 31, 2017. Both observations and simulations show that a daytime Es layer starting at ∼120 km in the morning descends to ∼100 km in the afternoon. In addition, the descending rate of the Es layer has obvious altitude and latitude dependence. The Es layer descends faster (∼2.1 km/h) at higher altitudes (above 110 km), and meanwhile, it descends relatively slowly (∼1.5 km/h) at low altitudes (below 110 km). The mean descending rate (∼1.5–1.8 km/h) of the Es layers gradually increases from Sanya to Mohe. It is undoubtedly that the wind shear convergence nodes controlled by the atmospheric tides can drive the Es layer to move downwards. However, the simulation results in this paper show that the wind shear convergence nodes and the Es layer traces do not overlap completely, especially in the vertical direction, which suggests that wind shear cannot fully explain the details of Es layer evolution. We should pay attention to the combined effect of wind shear and metallic ion density in future research, especially in the details of the evolution of Es layer in the vertical direction. Key Points: Both observations and simulations show that the Es layer traces and wind shear convergence nodes have a downward movement trend, which is mainly controlled by the atmosphere tides The Es layer's descending rates increase with altitude and latitude from Sanya to Mohe The Es layer traces observed by the ionosondes and the wind shear convergence nodes derived from the HWM14 model do not completely overlap, especially in the vertical direction